Analysis of the Compensation System in Indonesia - Riski Ramadani; Edi Marjan Nasution; Mhd. Ariel Zumaedi; Indah Wahyuni Pulungan; Nabila Riski Nst (Journal Research of Social Science, Economics, and Management, 2025)
This article analyzes the wage system in Indonesia by examining its historical development, regulatory framework, and Islamic perspective. Wages are a fundamental right of workers that function not only as compensation but also carry social, economic, and legal dimensions. The history of wages in Indonesia reflects a long journey from the discriminatory practices of the colonial era to the introduction of minimum wage policies in the 1970s, which have since evolved under recent regulations such as Government Regulation No. 36 of 2021. This study employs a qualitative approach using library research from academic literature, legal frameworks, and expert opinions. The findings show that Indonesia applies various wage systems, including time-based, output-based, and contract-based systems, all of which emphasize fairness, certainty, and the protection of workers' rights. Factors influencing wage determination include labor supply and demand, productivity, living costs, labor unions, company capacity, and government regulation. Nevertheless, challenges remain, such as the wage gap between formal and informal sectors, weak enforcement of regulations, and the insufficiency of minimum wages to meet decent living standards. From an Islamic perspective, wages are seen as a moral obligation that must be delivered fairly, promptly, and with respect for workers' dignity. Therefore, a balance between government regulation, business capacity, and workers' rights is essential to create harmonious industrial relations and ensure shared prosperity.